2020
DOI: 10.1080/16549716.2020.1715324
|View full text |Cite
|
Sign up to set email alerts
|

HIV-positive migrants’ experience of living in Sweden

Abstract: Background: There is a limited knowledge of the impact of being human immunodeficiency virus (HIV)-positive on migrants living in Sweden. It is therefore important to gain a general awareness of this issue in order to maintain the wellbeing of this vulnerable group of patients and to develop an adequate social support network. Objective: The aim of this study was to explore HIV-positive migrants' experiences of their life situations, living in Sweden. Method: A qualitative, exploratory study was performed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
0
6
0
2
Order By: Relevance
“…Previous Swedish studies also show challenges faced by migrants in terms of health inequalities due to different living conditions and experiences, which place them in different social positions with different degrees of vulnerability. [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous Swedish studies also show challenges faced by migrants in terms of health inequalities due to different living conditions and experiences, which place them in different social positions with different degrees of vulnerability. [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…However, it was not possible to get a clear picture of how migrants living with HIV in Sweden assessed their quality of life. A subsequent qualitative study in Sweden, however, suggested that they experienced loneliness, fear of disclosing HIV status, stigma and lack of a social network [ 20 ]. Another interview study that aimed to describing the experiences of migrants living with HIV and their encounters with the Swedish health-care system, showed that they appreciated free access to ARV, but required more time with their doctors.…”
Section: Introductionmentioning
confidence: 99%
“…To obtain insight into the role of stigma in recovery experiences of MEM with substance use problems, we conducted 34 in‐depth interviews in Flanders (Belgium). Participants were recruited through venue‐based methods (Mehdiyar, Andersson, & Hjelm, 2020) and the following inclusion criteria were applied: (1) being 18+ of age (adult age limit in Belgium), (2) self‐identifying as person with a migration background and/or belonging to an ethnic minority, and (3) having personal experience with recovery from problem substance use. Interviews were conducted in Dutch ( n = 29), English ( n = 4) and French ( n = 1).…”
Section: Methodsmentioning
confidence: 99%
“…In the study sample, we aimed to reflect the diversity of MEM in Flanders (Belgium) [ 23 ] through a purposive sampling strategy. Participants who self-identified as (1) having a migration and/or ethnic minority background and (2) being in recovery from problem substance use were recruited through venue-based methods [ 24 ] in Ghent and Antwerp (two ethnically diverse cities in Flanders). As MEM with substance use problems are considered a hard-to-reach population for research, we applied several strategies to overcome these barriers [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interview questions focused on participants’ (1) patterns of substance use, (2) their recovery process, (3) barriers and facilitators for recovery, and (4) the role of having a MEM background in this process. The open-ended questions that were complemented with probing follow-up questions, encouraged participants to talk openly about their lived experiences, unfolding rich narrative data in which recovery resources (or the lack thereof) became clear [ 24 ]. The interviews were conducted in places chosen by the study participants, such as their home, a treatment setting, coffee bar or a public library, where they felt comfortable to disclose personal experiences.…”
Section: Methodsmentioning
confidence: 99%